The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/0255-0857.136593
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial chronic endophthalmitis diagnosed by culture and molecular technique

Abstract: Accurate etiological diagnosis is the key to prevention of ocular morbidity in endophthalmitis cases. A 66 year old male was suffering from chronic endophthalmitis post-cataract surgery. Polymerase chain reaction examination on anterior chamber fluid was positive for Propionibacterium acnes but negative for the panfungal genome. He was advised vitrectomy with intravitreal injections. Polymerase chain reaction of vitreous aspirate was positive for P.acnes as well as panfungal genome. The vitreous sample also gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Surgical treatments were observed in 50% of this case series, which agrees with other studies that reported it in approximately 30% to 73% of cases (12,15,16,27,41). A de nitive initial surgical procedure should be considered in any patient with strong clinical evidence of severe or refractory CPE, or when the clinical features are suggestive or microbiologically proven aggressive microorganisms, such as fungal infection, Onchobactrum Anthropi, P.Acnes, or polymicrobial infection (15,22,26,34,45,52,(72)(73)(74)77).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatments were observed in 50% of this case series, which agrees with other studies that reported it in approximately 30% to 73% of cases (12,15,16,27,41). A de nitive initial surgical procedure should be considered in any patient with strong clinical evidence of severe or refractory CPE, or when the clinical features are suggestive or microbiologically proven aggressive microorganisms, such as fungal infection, Onchobactrum Anthropi, P.Acnes, or polymicrobial infection (15,22,26,34,45,52,(72)(73)(74)77).…”
Section: Discussionmentioning
confidence: 99%
“…Although Kluyveromyces marxianus is not usually a pathogen for human disease, it has been recovered from catheters, associated with canditdemia, and found in biofilms on many indwelling deovices such as prosthetic heart valves and pacemakers. K. marxianus has been seen in about 1% to 3% of cases with female genital infections, surgical wounds, and infections related to upper respiratory tracts [2,3].…”
Section: Introductionmentioning
confidence: 99%